2002
DOI: 10.1016/s0092-8674(01)00636-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of c-Myb–C/EBPβ Cooperation from Separated Sites on a Promoter

Abstract: c-Myb, but not avian myeloblastosis virus (AMV) v-Myb, cooperates with C/EBP beta to regulate transcription of myeloid-specific genes. To assess the structural basis for that difference, we determined the crystal structures of complexes comprised of the c-Myb or AMV v-Myb DNA-binding domain (DBD), the C/EBP beta DBD, and a promoter DNA fragment. Within the c-Myb complex, a DNA-bound C/EBP beta interacts with R2 of c-Myb bound to a different DNA fragment; point mutations in v-Myb R2 eliminate such interaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
152
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(159 citation statements)
references
References 50 publications
4
152
1
2
Order By: Relevance
“…It is possible that C/EBP b could influence transcription from this location either by interacting with NF-kB through long-range interactions with the promoter as has been shown for c-Myb 31 or through interaction with components of the RNA transcriptassociated heterogeneous nuclear ribonucleoprotein (hnRNP) complexes such as hnRNP K. 32 Further experiments are needed to address the specificity and functionality of C/EBP b binding to the þ 781T polymorphism in vivo. 6) and þ 781C allele (lanes 7-12) in EMSA with nuclear extracts from A549 cells harvested after no activation (NA) and after stimulation with TNF.…”
Section: Upregulation Of Ilmentioning
confidence: 99%
“…It is possible that C/EBP b could influence transcription from this location either by interacting with NF-kB through long-range interactions with the promoter as has been shown for c-Myb 31 or through interaction with components of the RNA transcriptassociated heterogeneous nuclear ribonucleoprotein (hnRNP) complexes such as hnRNP K. 32 Further experiments are needed to address the specificity and functionality of C/EBP b binding to the þ 781T polymorphism in vivo. 6) and þ 781C allele (lanes 7-12) in EMSA with nuclear extracts from A549 cells harvested after no activation (NA) and after stimulation with TNF.…”
Section: Upregulation Of Ilmentioning
confidence: 99%
“…Thus, the DNA-binding domain of B-Myb is not only required for protein-DNA interaction but also stimulates transcription via specific protein-protein interactions involving at leat two coactivators. That the Myb DNA-binding domain is involved in protein-protein interactions has also been shown in case of v-Myb and cMyb (Mink et al, 1996;Tahirov et al, 2002), whose interaction with members of the C/EBP transcription factor family is mediated by their DNA-binding domain. Previous work has shown that B-Myb directly interacts with the coactivator p300/CBP via the central part of B-Myb, which contains the transactivation domain (Horstmann et al, 2000b).…”
Section: Discussionmentioning
confidence: 72%
“…Alternatively, it is possible that the B cell specificity of the Ikaros and C/EBP complex may be mediated by a B cell-specific factor that was not detected in the current approach. In this respect, the synergistic interactions of Ikaros or C/EBP with other transcription factors have been previously observed in active regulation of different enhancers and promoters in lymphoid as well as other tissues [36,39]. Therefore, it will be necessary to identify this B cell-specific factor.…”
Section: Discussionmentioning
confidence: 96%